Implementation of Electronic Report Card Policy at Vocational High School 1 Palu - Hamid, Nurhayati; Djaelangkara, Rizali; Rahma, Agustian (Journal of Public Administration and Government, 2024)
This research aims to assess the implementation of the policy on electronic report cards at Vocational School Negeri 1 Palu. The research employs a qualitative descriptive method, which provides a detailed description of the phenomena or issues being studied at the research site based on existing facts. Data collection techniques include observation, in-depth interviews with informants, and documentation to gather the required primary and secondary data. The study involves 5 informants. The theoretical framework used in this research is George C. Edward III's theory, which includes four indicators for the implementation stage of the electronic report card policy at Vocational School Negeri 1 Palu. These indicators are Communication, Resources, Disposition, and Bureaucratic Structure. The research findings indicate that the implementation of the electronic report card policy at Vocational School Negeri 1 Palu is progressing fairly well, as evidenced by the Communication indicator, where information about the policy dissemination was directly obtained from the Ministry of Education regarding the implementation of the electronic report card program. Another successful indicator is the Bureaucratic Structure, as the policy implementation on the ground meets SOP standards through a guidebook provided directly by the Ministry of Education. However, the indicators for Resources and Disposition have not been adequately addressed. This is evident from the inadequate facilities and the lack of understanding among policy implementers about the urgency of the policy, leading to delays in the electronic report card program. These issues need to be addressed to ensure optimal overall implementation in the future.